2021
DOI: 10.31963/intek.v8i1.2801
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS and Antioxidant Capacity Analysis in Propanol Extract of Carthamus Tinctorious L

Abstract: Safflower, were extracted using propanol solvent at different time intervals: 10, 20, and 30 min at a constant temperature of 40°C. The extracts were analyzed by GC/MS technique. The major compounds identified were tetrapentacontane, tetracontane, triacontanol, gamma sitosterol, myristic acid, linoleic acid, stearic acid, palmitic acid, oleic acid, and lauric acid. However, some levels of palmidrol, beta-amyrin, cubenol, and tocopherol were also found in safflower extracts. Most of the volatile compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Tetracontane showed antibacterial against Staphylococcus aureus, Bacillus cereus, and Pseudomonas aeruginosa and antioxidant activity (Belkacemi et al, 2020). Therefore, Gollo et al (2020) and Indriati et al (2021) reported that extracts with tetracontane compounds indicated antioxidant activity. The antibacterial activity of flowers might be related to tetracontane in the extracts, as reported by Belkacemi et al (2020).…”
Section: Antimicrobial Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…Tetracontane showed antibacterial against Staphylococcus aureus, Bacillus cereus, and Pseudomonas aeruginosa and antioxidant activity (Belkacemi et al, 2020). Therefore, Gollo et al (2020) and Indriati et al (2021) reported that extracts with tetracontane compounds indicated antioxidant activity. The antibacterial activity of flowers might be related to tetracontane in the extracts, as reported by Belkacemi et al (2020).…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…Tetracontane is one of the major compounds which was only detected in flower samples at a retention time of 31.26 minutes with a peak area of 11.41%. Tetracontane is a natural product with anti-inflammatory, analgesic (Arora & Meena, 2017), antibacterial and antioxidant (Belkacemi et al, 2020;Indriati et al, 2021). Stigmast-5-en-3-ol, (3.beta.,24S)-(CAS) Clionasterol is known to have antiinflammatory, antipyretic, anti-ulcer, and antiarthritis (Arora & Meena, 2017).…”
Section: Analysis Of Bioactive Compounds On N-hexane Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-Steroidal, analgesics, anti-Inflammatory, antihypertensive, neuroprotective, antiviral,anticonvulsant, anti-oxidative 49 24…”
Section: Mome Inositolmentioning
confidence: 99%